EFFECT OF COMPETITIVE POWER TO TERM OF TRADE AND IMPLICATION TO STABILITY OF EXCHANGE IN INDONESIA - Francisca Sestri Goestjahjanti (Politeknik Negeri Semarang, 2017)
Indonesia's competitiveness as a determinant factor of the term of trade, that has been declining in recent years, due to the sluggish world trade triggered by the economic slowdown in China, as well as the increamental of the Fed’s interest rate, is very influence to stability of the exchange rate in Indonesia. The purpose of this research is to analyze and assess the influence ofthe competitiveness effects on the term of trade, and its impact to stability of the exchange rate in Indonesia. The secondary data of the research is time series for 22 years from 1995 until 2016. The research method used is explanatory research to explain the causal relationship between variables in a model, through hypothesis test. Analytical technique used linear regression. The result of the research shows significant influence between the competitiveness variable on the term of trade, and its impact has significant effect to stability of the exchange rate in Indonesia